Investigation on the Effect of Drive Train System for Archimedes Screw Turbine - Nurul Suraya, Azahari; Ummu Kulthum, Jamaludin; N. M. M., Ammar (2016)
Nowadays, the Archimedes screw turbine has become one of alternative in generating electricity. It is low in terms of cost and sourceful as the Earth is covered more than 70% of water. The objective of this study is to investigate the effect of the drive train system that may influence, power generated from the Archimedes screw turbine. This paper focused on studying the relationship between drive train system and rotational speed. An experiment was conducted with two different types of drive train system to compare the rotational speed of the turbine at the same flow rate range from 0.012 m³/s to 0.016 m³/s (diameter of driver Pulley A is 102mm and diameter of driver Pulley B is 150mm). By increasing the diameter of the driver pulley up to 150mm, the maximum power generated of 0.444 Watts at low rotational per minutes (RPM) of 70. In conclusion, increase the diameter of driver pulley requires low RPM to produce maximum power output.